D, Dampak Tata Niaga Cengkeh terhadap Pabrik Rokok Jambu Bol Kudus 1992 - 1998 - Muhammad Afif Abdullah; Bambang Rakhmanto (UNIVERSITAS MUHAMMADIYAH METRO, 2027)
This study examines the impact of the clove trade policy implemented through the Clove Buffer and Marketing Agency (BPPC) on the Jambu Bol Cigarette Factory in Kudus during the period 1992–1998. The research employs the historical method with an economic history approach and applies Richard Robison's concept of crony capitalism as the analytical framework. Data were collected from the company's internal production records (1987–2000), government regulations on the clove trade, contemporary newspaper reports, and oral history interviews with former employees of the Jambu Bol Cigarette Factory. The findings indicate that the establishment of BPPC transformed the clove trade from a relatively open market into a centralized distribution system. This policy restricted the factory's access to raw materials, increased production costs, and created distribution and administrative obstacles that disrupted production activities. As a result, the factory's production declined from 1.92 billion cigarettes in 1992 to 790.37 million cigarettes in 1997, representing a decrease of more than 59 percent. The decline in production also reduced working hours and workers' incomes. Following the dissolution of BPPC in 1998, the company's production recovered significantly, although the recovery was also influenced by broader national economic and political changes. This study demonstrates that the New Order's clove trade policy affected not only clove farmers as producers but also the sustainability of medium-scale kretek cigarette manufacturers and the socio-economic conditions of their workers.